Potential of Developing Community-based Ecotourism in Van Don District, Quang Ninh Province - Hoa, Tran Thi Mai; Huan, Nguyen Cao; Haruo, Noma (VNU Journal of Science: Earth and Environmental Sciences; Vol 26 No 3, 2010)
Abstract. Ecotourism is said to be a high prospective trend in tourism development. Theoretically, it addresses the triple bottom line of the World’s pressing issues. Nevertheless, the reality does not usually come up to expectations. Very few case studies were proved to be successfully adopted. One of the reasons is the weakness in terms of community approach, particularly in developing countries. In Vietnam, the problem is even more serious due to the fact that residents are rarely aware of their right in tourism planning and their responsibility towards the environment, as well as a shortage of a common information channel among a local government, tourism enterprises and citizens. As a result, the development of the so-called ecotourism destinations, which have wildly boomed, has little to do with benefit-sharing with local people, who are assumed to be the key to sustainable development. By assessing the potential of community-based ecotourism in Van Don, focusing on Bai Tu Long National Park, this paper will suggest some guidelines for the establishment of an ecotourism site at the very early stage to order to avoid distorted development. Efforts are made to emphasize on a more proactive role the inhabitants should play in the tourism industry to improve their own life as well as their native land. Keywords: ecotourism, community approach, Bai Tu Long, National Park, Van Don.